Standardization of process for hairy root production using Agrobacterium rhizogenes for monoxenic culture of arbuscular mycorrhizal fungi - DEVIKRISHNA, S; KUMUTHA, K; SANTHANAKRISHNAN, P; PRIYA, L SRIMATHI (The Indian Journal of Agricultural Sciences, 2010)
Arbuscular mycorrhizal fungi are ubiquitous and form symbiosis with roots of plants and which cannot be pure cultured as it is an obligate fungi but can be cultured in vitro under root organ culture. Cowpea (Vigna unguiculata L. Walp) and tomato (Solanum lycopersicum L. Mill) explants were selected for hairy root production and conditions were standardized for media, incubation time and light based on the induction frequency of Ri T-DNA transformed hairy root through Agrobacterium rhizogenes. Different A. rhizogenes strain, viz 532, 2364 were used to induce hairy roots. A. rhizogenes 532 induced maximum hairy roots in cowpea, whereas 2 364 induced more hairy roots in tomato. Out of 3 different media evaluated, Modified White’s medium supported more induction of hairy roots in cowpea and tomato. Manual wounding of explants with the addition of 100 μM acetosyringone in the media resulted better induction of hairy roots in both the explants with both the strains of A. rhizogenes. Also 48 hr of incubation in dark conditions produced maximum hairy root frequency for both strains using cowpea and tomato explants. These transformed hairy roots can serve as potential host for in vitro culturing of Arbuscular mycorrhizal fungus.